Risk of Colonization with Multidrug-Resistant Gram-Negative Bacteria Among Travellers and Migrants: A Narrative Review - Diogo Mendes Pedro; Daniela Santos; Maria Meneses; Fátima Gonçalves; Gonçalo Jantarada Domingos; Cátia Caneiras (Tropical Medicine and Infectious Disease)
Globalization in the 21st century has posed several challenges. In particular, the spread of multidrug-resistant bacterial strains, especially Gram-negative bacteria, which are prevalent in certain regions of the world, is one of the most critical issues. This raises concerns about the risks associated with the booming tourism industry and migratory flows. In fact, even transient colonization with multidrug-resistant strains can present significant challenges to individual, family, and public health. Understanding the epidemiology and mechanisms of resistance, associated risk factors and prevention policies is therefore essential to ensure that strategies are in place to limit the global spread of high-risk bacterial clones and thereby protect public health.